2012
DOI: 10.1302/0301-620x.94b8.28717
|View full text |Cite
|
Sign up to set email alerts
|

Cost savings of using a cemented total hip replacement

Abstract: The debate whether to use cemented or uncemented components in primary total hip replacement (THR) has not yet been considered with reference to the cost implications to the National Health Service. We obtained the number of cemented and uncemented components implanted in 2009 from the National Joint Registry for England and Wales. The cost of each component was established. The initial financial saving if all were cemented was then calculated. Subsequently the five-year rates of revision for each type of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Three NJR-based retrospective cohort studies [16, 21, 22] and one review [23] discussed the economic aspects in the choice of whether or not to use cement. Of these, two [16, 21] considered the differences in cost after cemented or hybrid and two [22, 23] after cemented or completely cementless THA. Taking into account material costs and costs associated with differences in revision rates, the cemented prostheses were the cheapest option in every single article.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three NJR-based retrospective cohort studies [16, 21, 22] and one review [23] discussed the economic aspects in the choice of whether or not to use cement. Of these, two [16, 21] considered the differences in cost after cemented or hybrid and two [22, 23] after cemented or completely cementless THA. Taking into account material costs and costs associated with differences in revision rates, the cemented prostheses were the cheapest option in every single article.…”
Section: Resultsmentioning
confidence: 99%
“…Although the cement itself was an additional cost for cemented THA (107 pounds for four cement mixes), this cost was relatively small compared to the much more expensive components (polyethylene liner and metal shell) used for cementless fixation of the acetabulum [16]. When comparing cemented with fully cementless THA, a third study [22] showed that if in England all hip prostheses would be cemented, 10 million pounds in material costs would be saved each year, with an additional saving of 8.5 million pounds in the five following years because of the lower risk of revision after cemented compared to cementless THA. In this study, the average cost of a cemented acetabular component was 285 pounds (79–1077 pounds) and that of a cementless component was 511 pounds (100–1288 pounds).…”
Section: Resultsmentioning
confidence: 99%
“…The 8th Annual National Joint Registry Report found that the cost of a primary cemented femoral component plus the associated cement and accessories is £820 per THA, whereas the cost of a primary cementless femoral component was £915 per THA [46], [47]. Similar data from the United States agree that cementless femoral prostheses are consistently more expensive than cemented femoral prostheses even when including the cost of cement plus accessories [14].…”
Section: Discussionmentioning
confidence: 97%
“…A comprehensive cost comparison between cemented and uncemented implants calculated a saving of £18.5 million over 5 years if all implants used were cemented prosthesis. 18 The mean cost of cemented acetabular components was £285 and uncemented components had a mean cost of £511. 18 Although this project only assessed costs in primary surgery; the cost of revision trabecular metal shells is substantially higher than the cost of primary uncemented acetabular components.…”
Section: Discussionmentioning
confidence: 99%